The Importance of Oral Health Education for Kindergarten Students in Rural Areas - Widyatama, Rendra; Ananda, Dhiaksa Adhi; Ananda, Vidya; Yuniasih, Dewi (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Oral health is essential for overall human well-being. Everyone, regardless of age—whether young or old—must maintain good dental hygiene, including kindergarten children in rural areas. Unfortunately, knowledge of oral health and tooth-brushing skills among kindergarten students in these regions remains inadequate. To improve their understanding of dental health and proper brushing techniques, effective educational methods are required. In response to this issue, a community service team implemented a multi-method approach targeting two groups: primary and secondary beneficiaries. The primary group consisted of kindergarten students, who were engaged through interactive counseling, demonstrations, question-and-answer sessions, singing, games, rewards, and practical tooth-brushing exercises. Meanwhile, for the secondary group—teachers and parents—the team utilized persuasive communication via WhatsApp messages, providing oral health education and encouraging parents to consistently remind their children to practice proper dental hygiene daily. Based on the program evaluation, the multi-method approach was proven effective in enhancing both the knowledge and skills of kindergarten children in maintaining oral health. Furthermore, it contributed to creating an environment that fosters healthy behavior among children. Therefore, the team believes that dental health practitioners and educators can adopt similar methods to achieve optimal outcomes in promoting oral health awareness.